Ovarian cystadenofibroma mimicking malignancy: role of frozen section - a case report - Antil, Sarvottma (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Ovarian cystadenofibroma is a rare benign neoplasia whose radiological and macroscopic appearance mimicks malignancy. This case report highlights the importance of intraoperative frozen section in avoiding an inappropriate extensive surgery for this benign disease. A case study of 28 year old unmarried female with a complex unilateral ovarian cyst, with radiological features suggestive of malignancy. Laparoscopic cystectomy was carried out and an intraoperative frozen section of the tissue was ordered. Frozen section examination pointed towards the benign nature of the tumor and hence inappropriate extensive surgery was avoided. A benign tumor like ovarian cystadenofibroma, which otherwise mimicks malignancy, can be proven to be benign by an intraoperative frozen section examination. Hence an unnecessary aggressive surgical management can be avoided.